A numerical human brain phantom for dynamic glucose‐enhanced (DGE) MRI: On the influence of head motion at 3T. Issue 5 (29th December 2022) - Lehmann, Patrick M.; Seidemo, Anina; Andersen, Mads; Xu, Xiang; Li, Xu; Yadav, Nirbhay N.; Wirestam, Ronnie; Liebig, Patrick; Testud, Frederik; Sundgren, Pia; van Zijl, Peter C. M.; Knutsson, Linda
Abstract : Purpose: Dynamic glucose‐enhanced (DGE) MRI relates to a group of exchange‐based MRI techniques where the uptake of glucose analogues is studied dynamically. However, motion artifacts can be mistaken for true DGE effects, while motion correction may alter true signal effects. The aim was to design a numerical human brain phantom to simulate a realistic DGE MRI protocol at 3T that can be used to assess the influence of head movement on the signal before and after retrospective motion correction. Methods: MPRAGE data from a tumor patient were used to simulate dynamic Z‐spectra under the influence of motion. The DGE responses for different tissue types were simulated, creating a ground truth. Rigid head movement patterns were applied as well as physiological dilatation and pulsation of the lateral ventricles and head‐motion‐induced B0 ‐changes in presence of first‐order shimming. The effect of retrospective motion correction was evaluated. Results: Motion artifacts similar to those previously reported for in vivo DGE data could be reproduced. Head movement of 1 mm translation and 1.5 degrees rotation led to a pseudo‐DGE effect on the order of 1% signal change. B0 effects due to head motion altered DGE changes due to a shift in the water saturation spectrum. Pseudo DGE effects were partly reduced or enhanced by rigid motion correction depending on tissue location. Conclusion: DGE MRI studies can be corrupted by motion artifacts. Designing post‐processing methods using retrospective motion correction including B0 correction will be crucial for clinical implementation. The proposed phantom should be useful for evaluation and optimization of such techniques.